การพัฒนาตัวบ่งชี้การบริหารงานวิจัย มหาวิทยาลัยนวมินทราธิราช - มงคลสินธุ์ วณิดา; แสงเลิศอุทัย จิตติรัตน์; ศรีโสภา โยธิน (Journal of Research and Curriculum Development, 2019)
This research had the objectives to develop indicators for research management at Navamindradhiraj University, tested the goodness of fit of the indicators with the empirical data, and made the university’s policy suggestions. The method used consisted of 3 procedures: 1) establishment of appropriate indicators, 2) evaluation of the suitability and feasibility of the indicators by using a confirmatory factor analysis (CFA) and a connoisseurship seminar, and 3) policy recommendations by organizing a meeting of universities’ administrators, practitioners, and clients. The results of the research found that the suitable indicators consist of 5 aspects: clients, people, policy, finance and internal process. The indicators had good fit with the empirical data. The policy suggestion was to produce a master plan for integration and evaluate inclusive management.